О строении снабберной защиты модуля IGB-транзисторного чоппера - Синчук, Олег Николаевич; Синчук, Игорь Олегович; Будников, Всеволод Николаевич; Черная, Виктория Олеговна (НТУ "ХПИ", 2014)
Рассмотрены возможные причины возникновения и развития аварийных режимов функционирования тяговых электроприводов. Обоснована необходимость исследований и оценки критериев комплекса защит модулей тяговых IGB-преобразователей от нештатных режимов функционирования при питании от тяговой контактной сети и Г-образного входного фильтра. Предложен способ защиты транзисторных модулей от аварийных ситуаций.

The article reviewed potential reasons of occurrence and development of emergency operation modes of traction motor drives. The necessity of performing researches and evaluating criteria of module protection complex of traction IGB converter against abnormal operating mode at delivery of energy from traction overhead system and L-shaped inlet filter is proved. Safety method of transistor modules against emergency situations was suggested. Operation peculiarities of pulse converter with safety system against emergency situations are reviewed.
On the constitution of the snubbermodule protection IGB-transistor converters
Keywords: преобразователь; электропривод тяговый; электровоз; режим аварийный; замыкание короткое; converter; traction motor drive; electric locomotive; emergency mode; short circuit